DEVELOPMENT OF A MULTIPLE-CHOICE ITEM ANALYSIS APPLICATION TO ENHANCE LEARNING ASSESSMENT INSTRUMENTS - Hilyah Ashoumi; Siti Citra Aulia Aprina; Muhammad Kris Yuan Hidayatulloh; Munifah Munifah; Iskandar Tsani (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
The research aimed to ascertain the viability, receptivity of teachers to the implementation of multiple-choice item analysis and to develop a multiple-choice item analysis application in desktop form. This type of research was developed using the research and development (R&D) method. This research employs the ADDIE development model, which comprised five stages. The phases of analysis, design, development, implementation, and evaluation were employed. The results of this research indicated that the level of feasibility, based on the first media expert with a percentage value of 85%, was declared "Very Eligible"; the second media expert, with a percentage value of 86.66%, was declared "Very Eligible"; and the third media expert, with a percentage value of 95%, was declared "Very Appropriate." In contrast, the response results from teachers received a percentage value of 80.5%. It indicated the application was suitable for use in educational institutions. The findings showed that the multiple-choice item analysis application had great potential to improve the quality of test questions in schools. The application overcame the weaknesses of existing software by offering a reliable, easy-to-use tool, supported by high ratings from experts and positive feedback from teachers. This innovation helped educators create better assessments, improving learning outcomes and overall education quality. The implication of this research was that the developed application can serve as a practical solution for schools to strengthen assessment quality, enhance teachers’ competency in test construction, and support policy-making in education by providing accurate data-driven insights into student learning outcomes.